2019
DOI: 10.1002/mc.23022
|View full text |Cite
|
Sign up to set email alerts
|

Exosome‐transmitted p120‐catenin suppresses hepatocellular carcinoma progression via STAT3 pathways

Abstract: Hepatocellular carcinoma (HCC) is a fatal disease with increasing morbidity and poor prognosis due to surgical recurrence and metastasis. Moreover, the molecular mechanism of HCC progression remains unclear. Although the role of p120-catenin (p120ctn) in liver cancer is well studied, the effects of secreted p120ctn transported by exosomes are less understood. Here, we show that p120ctn in exosomes secreted from liver cancer cells suppresses HCC cell proliferation and metastasis and expansion of liver cancer st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…84 In contrast, p120-catenin in exosomes secreted by HCC (hepatocellular carcinoma) cells inhibited the proliferation, metastasis, and expansion of HCC CSCs. 85 Exosomes are also important participants in the resistance of CSCs, which involving multiple mechanisms, including enhanced DNA repair efficiency and anti-apoptotic capacity, slow cell cycle progression, drug efflux, and expression of detoxifying enzymes. 86 For example, in PC, BxR-CSC (GEM-resistant BxPC-3 cells)-derived exosomes induced GEM resistance, inhibited GEM-induced cell cycle arrest, and antagonized GEM-induced apoptosis.…”
Section: Exosome and Cancer-associated Fibroblastsmentioning
confidence: 99%
“…84 In contrast, p120-catenin in exosomes secreted by HCC (hepatocellular carcinoma) cells inhibited the proliferation, metastasis, and expansion of HCC CSCs. 85 Exosomes are also important participants in the resistance of CSCs, which involving multiple mechanisms, including enhanced DNA repair efficiency and anti-apoptotic capacity, slow cell cycle progression, drug efflux, and expression of detoxifying enzymes. 86 For example, in PC, BxR-CSC (GEM-resistant BxPC-3 cells)-derived exosomes induced GEM resistance, inhibited GEM-induced cell cycle arrest, and antagonized GEM-induced apoptosis.…”
Section: Exosome and Cancer-associated Fibroblastsmentioning
confidence: 99%
“…Numerous studies demonstrated that the JAK/STAT3 signaling pathway is constitutively activated in human gastric cancer, while STAT3 activity is rapid and short-lived in normal cells [21][22]. Cytokines such as interferons, interleukins, and growth factors, bind to cell surface receptors and activate JAKs [23][24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that exosomes carry and translocate membrane proteins from tumor cells in one organ to healthy cells in other organs to serve as seed surface receptors for the landing and proliferation of migrated cancer cells [ 126 ]. The membrane protein, p120-Catenin (p120ctn), is downregulated in exosomes exocytosed by hepatocellular carcinoma cells (HCCs), as compared to exosomes exocytosed by healthy liver cells [ 127 ], implying that the downregulation of p120ctn simulates tumor growth and progression. HCCs treated with exosomes isolated from hepatoma cells transfected with p120ctn-overexpressing lentivirus formed fewer colonies and inhibited the proliferation and migration of HCCs.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%